High-Performance Thin-Layer Chromatography for Rutin, Chlorogenic Acid, Caffeic Acid, Ursolic Acid, and Stigmasterol Analysis in Periploca aphylla Extracts - Raha Orfali; Shagufta Perveen; Hanan Y. Aati; Perwez Alam; Omar M. Noman; Javier Palacios; Bayan Salem S. Al-Kurbi; Areej M. Al-Taweel; Afsar Khan; Rashad Mehmood; Shabana Iqrar Khan (Separations, 2021)
Periploca aphylla (PA), an interesting Saudi medicinal plant, is used in folk medicine to treat urticaria, cerebral fever, tumors, and swelling. To prove its use in folk medicine, two different extracts from the aerial parts of the plant: chloroform P-1, and n-butanol P-2 were subjected to biological assays to screen peroxisome proliferator-activated receptors (PPARα and PPARγ) agnostic, anti-inflammatory, antioxidant, cytotoxic, and estrogenic activities. In addition, five bioactive secondary metabolites were isolated from the aerial parts of the plant: rutin, chlorogenic acid, caffeic acid, ursolic acid, and stigmasterol. P-1 and P-2 decreased cellular oxidative stress by 47.0% and 62.0%, respectively, compared to the standard drug quercetin, while one of the compounds rutin PA-1 isolated from P-1 extract and significantly decreased cellular oxidative stress by 67.0% compared to quercetin (75.0%). P-1 and P-2 also significantly activated PPARγ agnostic. P-1 and P-2 did not inhibit nuclear factor kappa B and inducible nitric oxide synthase activity and showed no cytotoxic or estergenic effects on four human cancer cell lines. In this study, both extracts were standardized using high-performance thin-layer chromatography (HPTLC). RP-HPTLC showed sharp and compact bands of rutin (Rf = 0.09), caffeic acid (Rf = 0.25), and chlorogenic acid (Rf = 0.39) scanned at λmax = 340 nm using the water: methanol (60:40 v/v) mobile phase. At λmax = 539 nm ursolic acid (Rf = 0.20) and stigmasterol (Rf = 0.48) were scanned using the chloroform: methanol (98:2 v/v) as NP-HPTLC mobile phase. Therefore, the developed RP- and NP-HPTLC systems are a precise, sensitive, and specific analytical tool for the quantification of compounds isolated from PA, which can be used as phytomarkers for taxonomical identification and assessment of PA.